Transportation and logistics cluster competitive advantages in the U.S. regions: A cross-sectional and spatio-temporal analysis. (March 2017) - Kumar, Indraneel; Zhalnin, Andrey; Kim, Ayoung; Beaulieu, Lionel J.
Abstract: This article applies spatial cluster and econometric analyses to study attributes of the transportation and logistics cluster regions across the continental U.S., focusing on jobs, clustering, and dispersal patterns. Two questions are examined: 1) Is transport and logistics specialization a primary feature of large urban metropolitan regions or do rural nonmetropolitan regions (be they micropolitan or noncore) have the capacity to support this type of cluster? 2) Does transport infrastructure explain jobs in the transportation and logistics cluster? The research employs a county level lattice data of transportation and logistics cluster jobs from 2008 to 2012 as well as transport infrastructure variables. The findings reveal that the transportation and logistics clusters are concentrated primarily in metropolitan areas, and to some degree, in nonmetropolitan regions of the U.S. In addition, the transport infrastructure is found to have a positive impact on jobs in the transportation and logistics clusters over the period of the study. Intermodals have the largest effect on jobs, followed by airports, annual average daily traffic on the National Highway Planning Network, railroads, and ports.